Multivariable Regression and Adaptive Neurofuzzy Inference System Predictions of Ash Fusion Temperatures Using Ash Chemical Composition of US Coals. (22nd May 2014) - Karimi, Shahab; Jorjani, Esmaeil; Chehreh Chelgani, Saeed; Mesroghli, Shahin
Abstract : In this study, the effects of ratios of dolomite, base/acid, silica, SiO2 /Al2 O3, and Fe2 O3 /CaO, base and acid oxides, and 11 oxides (SiO2, Al2 O3, CaO, MgO, MnO, Na2 O, K2 O, Fe2 O3, TiO2, P2 O5, and SO3 ) on ash fusion temperatures for 1040 US coal samples from 12 states were evaluated using regression and adaptive neurofuzzy inference system (ANFIS) methods. Different combinations of independent variables were examined to predict ash fusion temperatures in the multivariable procedure. The combination of the "11 oxides + (Base/Acid) + Silica ratio" was the best predictor. Correlation coefficients (R 2 ) of 0.891, 0.917, and 0.94 were achieved using nonlinear equations for the prediction of initial deformation temperature (IDT), softening temperature (ST), and fluid temperature (FT), respectively. The mentioned "best predictor" was used as input to the ANFIS system as well, and the correlation coefficients (R 2 ) of the prediction were enhanced to 0.97, 0.98, and 0.99 for IDT, ST, and FT, respectively. The prediction precision that was achieved in this work exceeded that reported in previously published works.